TikTok and children: An Introduction - Lee, jin; Abidin, crystal; Leaver, Tama (SAGE, 2025)
TikTok's global popularity among children has sparked intense debate worldwide. Some argue that the platform's algorithmic design leads children down a rabbit hole of compulsive content consumption and encourages the imitation of socially harmful behaviours. Others highlight its positive role as a space for children to express their voices on social issues and engage in socialization. This Special Issue on TikTok and Children arises within this context as an attempt to explore the complicated issues surrounding the presence of children on TikTok, their usage of the app, and the cultures they partake in and proliferate on the platform. By showcasing a range of topics, methodologies, and disciplinary framings on how to study children and TikTok, the Special Issue provides a meaningful opportunity to think about balanced and practical approaches to maximise children's rights and agency, and to leverage on the range of platform cultures for positive child development.